Biomineralization of PbS and PbS–CdS core–shell nanocrystals and their application in quantum dot sensitized solar cells. Issue 16 (8th April 2016) - Spangler, Leah C.; Lu, Li; Kiely, Christopher J.; Berger, Bryan W.; McIntosh, Steven
Abstract : Biomineralization is demonstrated as a facile aqueous route to the synthesis of PbS and PbS–CdS core–shell quantum dot nanocrystals. Abstract : Biomineralization utilizes biological systems to synthesize functional inorganic materials for application in diverse fields. In the current work, we enable biomineralization of quantum confined PbS and PbS–CdS core–shell nanocrystals and demonstrate their application in quantum dot sensitized solar cells (QDSSCs). An engineered strain of Stenotrophomonas maltophilia is utilized to generate a cystathionine γ-lyase that is active for the biomineralization of metal sulfide nanocrystals from a buffered aqueous solution of metal salts andl -cysteine. In the presence of lead acetate, this enzymatic route generates rock salt structured PbS nanocrystals. Controlling the growth conditions yields ∼4 nm PbS crystals with absorption and photoluminescence peaks at 910 nm and 1080 nm, respectively, consistent with the expected strong quantum confinement of PbS at this size. Quantum yields (QY) of the biomineralized PbS quantum dots, determined after phase transfer to the organic phase, range between 16 and 45%. These are the highest reported QY values for any biomineralized quantum dot materials to date and are comparable with QYs reported for chemically synthesized materials. Subsequent exposure to cadmium acetate results in the biomineralization of a thin CdS shell on the PbS core with a resultant blue-shift in optical properties. The photoluminescence peak shifts to 980 nm, consistent with the expected decrease in band gap energy of a PbS–CdS core–shell heterostructured quantum dot. HAADF-STEM imaging confirms the crystalline structure and size of the particles with complimentary XEDS analysis confirming the presence of Cd, Pb, and S in individual nanocrystals. Integration of these QDs into QDSSCs yields open circuit potentials of 0.43 V and 0.59 V for PbS and PbS–CdS, respectively, consistent with expectations for these materials and previously reported values for chemically synthesized QDs.